Spatiotemporal dynamics and driving mechanism of eco-environmental quality in piedmont-oasis-desert ecotone based on long-term harmonized remote sensing ecological index- take Korla - Tiemenguan oasis in Xinjiang as an example - Junling He; Xifeng Ju; Chuqiao Han; Liming Liu; Haidong Zhang; Saitiniyazi Adilai; Chongbo Li (Environmental and Sustainability Indicators)
Eco-environmental quality is the basic premise of oasis socio-economic development. Clarifying the spatiotemporal dynamic pattern and evolution mechanism in the piedmont-oasis-desert ecotone is a basis for regional development. To solve this problem, the Korla- Tiemengguan piedmont-oasis-desert ecotone, located between the southern foot of the Tianshan Mountain and the northern edge of the Taklimakan Desert in Xinjiang, China, was selected in this study. Meanwhile, this study proposed an oasis remote sensing ecological index (ORSEI), which considered the influence of salinization and explored the spatiotemporal pattern with long-term harmonized Landsat. Secondly, the spatial patterns were identified by trend analysis, coefficient of variation, and spatiotemporal migration model. Finally, the explanatory power was quantified, and the evolution trend was further discussed. The results showed: (1) the ORSEI had a strong correlation with RSEI (R = 0.93), but the ORSEI had better performance in the ecotone and could reflect more details. (2) In spatial distribution, the mean ORSEI was 0.334, and the central oasis was better than the northern mountainous and the southern desert. Time series showed a fluctuating upward trend, the mean value increased from 0.203 in 1991 to 0.383 in 2020. (3) The improvement area was concentrated in the central area, accounting for 46.798%, and the fluctuation of the improvement area was high. The degraded and essential stable areas were located in the northern and the southern, accounting for about 25% of the total area, and the overall fluctuation was low. (4) The spatiotemporal distribution results from the joint action of natural and human factors, the key factors were temperature, precipitation, and socio-economic development level. This study can provide ideas and methods for ecological governance and basis for the implementation of ecological protection and restoration projects.